Tumbuhan Obat yang Ditemukan di Dataran Tinggi Kabupaten Solok - Rahmayenti, Sintia; ., Nursyahra; ., Zikra (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to determine the types of plants, plant parts and methods of processing medicinal plants used by the community in Nagari Sungai Nanam. Knowledge of medicinal plants was identified based on directions from herbalists in the village. This research method is a descriptive survey method where researchers carry out direct field observations. Medicinal plant species were identified in the field and continued at the Botany Laboratory of PGRI University, West Sumatra. The results of the research that was carried out showed that 36 families with 71 species of plants were used as medicine. The parts of the plants used varied from the shoots to the roots. There are also processing methods such as boiling, pounding, mixing, blending, pressing and brewing, but not all medicinal plants found in Nagari Sungai Nanam are used as medicine in other places, so this knowledge can be used as knowledge that needs to be preserved.